Retinol binding protein 4 and type 2 diabetes: from insulin resistance to pancreatic β-cell function - Fan, Jiahua; Hu, Jinxing (Endocrine, 2024)
Background and aim Retinol binding protein 4 (RBP4) is an adipokine that has been explored as a key biomarker of type 2 diabetes mellitus (T2DM) in recent years. Researchers have conducted a series of experiments to understand the interplay between RBP4 and T2DM, including its role in insulin resistance and pancreatic β-cell function. The results of these studies indicate that RBP4 has a significant influence on T2DM and is considered a potential biomarker of T2DM. However, there have also been some controversies about the relationship between RBP4 levels and T2DM. In this review, we update and summarize recent studies focused on the relationship between RBP4 and T2DM and its role in insulin resistance and pancreatic β-cell function to clarify the existing controversy and provide evidence for future studies. We also assessed the potential therapeutic applications of RBP4 in treating T2DM. Methods A narrative review. Results Overall, there were significant associations between RBP4 levels, insulin resistance, pancreatic β-cell function, and T2DM. Conclusions More mechanistic studies are needed to determine the role of RBP4 in the onset of T2DM, especially in terms of pancreatic β-cell function. In addition, further studies are required to evaluate the effects of drug intervention, lifestyle intervention, and bariatric surgery on RBP4 levels to control T2DM and the role of reducing RBP4 levels in improving insulin sensitivity and pancreatic β-cell function.